Association between TP53 codon 72 G>C Polymorphism and Thyroid Carcinoma Risk: An Up-to-Date Meta-Analysis - Jafari Nedooshan, Jamal; Yazdi, Mohammad Forat; Neamatzadeh, Hossein; Zare Shehneh, Masoud; Kargar, Saeed; Seddighi, Niloofar (Asian Pacific Journal of Cancer Biology, 2016)
Objective: Many published data on the association between p53 codon 72 G>C polymorphism and thyroid carcinoma risk showed inconclusive results. The aim this study was to assess the association between p53 codon 72 G>C polymorphism and thyroid cancer risk. Methods: A literature search of PubMed, EMBASE, Google scholar and Web of Science databases for case–control studies examining the association between p53 codon 72 G>C polymorphism and thyroid cancer susceptibility up October 2016 was performed. Odds ratios (OR) with 95 % confidence intervals (95 % CI) were used to assess the strength of the association. Results: A total of 12 case–control studies involving 2,062 thyroid cancer patients and 3,027 controls were included. There was a significant association between the p53 codon 72 G>C polymorphism and thyroid cancer susceptibility in the overall populations under homozygote (CC vs. GG: OR = 1.18, 95% CI 1.12-3.05, P = 0.01) and recessive model (CC vs. GC+GG: OR = 1.73, 95% CI 1.16-2.59, P = 0.007). Subgroup analysis by ethnicity showed that there was no significant association between p53 codon 72 G>C polymorphism and thyroid cancer risk in Caucasians, Asians and mixed Brazilian. No significant publication bias was observed by using Begg’s funnel plot and Egger’s test. Conclusion: Present meta-analysis indicated that the p53 codon 72 G>C polymorphism may be associated with thyroid cancer risk. However, more studies with large sample size are needed to further assess the associations.